Multiple Brain Networks Mediating Stimulus–Pain Relationships in Humans. (26th March 2020) - Geuter, Stephan; Reynolds Losin, Elizabeth A; Roy, Mathieu; Atlas, Lauren Y; Schmidt, Liane; Krishnan, Anjali; Koban, Leonie; Wager, Tor D; Lindquist, Martin A
Abstract: The brain transforms nociceptive input into a complex pain experience comprised of sensory, affective, motivational, and cognitive components. However, it is still unclear how pain arises from nociceptive input and which brain networks coordinate to generate pain experiences. We introduce a new high-dimensional mediation analysis technique to estimate distributed, network-level patterns that formally mediate the relationship between stimulus intensity and pain. We applied the model to a large-scale analysis of functional magnetic resonance imaging data ( N = 284), focusing on brain mediators of the relationship between noxious stimulus intensity and trial-to-trial variation in pain reports. We identify mediators in both traditional nociceptive pathways and in prefrontal, midbrain, striatal, and default-mode regions unrelated to nociception in standard analyses. The whole-brain mediators are specific for pain versus aversive sounds and are organized into five functional networks. Brain mediators predicted pain ratings better than previous brain measures, including the neurologic pain signature (Wager et al. 2013 ). Our results provide a broader view of the networks underlying pain experience, as well as novel brain targets for interventions.